Cemdata18: A chemical thermodynamic database for hydrated Portland cements and alkali-activated materials - Lothenbach, Barbara; Kulik, Dmitrii A.; Matschei, Thomas; Balonis, Magdalena; Baquerizo, Luis; Dilnesa, Belay; Miron, George D.; Myers, Rupert J. (Cement and concrete research, 2019)
Thermodynamic modelling can reliably predict hydrated cement phase assemblages and chemical compositions, including their interactions with prevailing service environments, provided an accurate and complete thermodynamic database is used. Here, we summarise the Cemdata18 database, which has been developed specifically for hydrated Portland, calcium aluminate, calcium sulfoaluminate and blended cements, as well as for alkali-activated materials. It is available in GEMS and PHREEQC computer program formats, and includes thermodynamic properties determined from various experimental data published in recent years. Cemdata18 contains thermodynamic data for common cement hydrates such as C-S-H, AFm and AFt phases, hydrogarnet, hydrotalcite, zeolites, and M-S-H that are valid over temperatures ranging from 0 to at least 100 °C. Solid solution models for AFm, AFt, C-S-H, and M-S-H are also included in the Cemdata18 database.